Nós mulheres negras: determinações do capitalismo, racismo e sexismo nas condições de trabalho e de vida das mulheres negras atendidas nas Varas de violência doméstica do TJSP - Santana, Lucinete Rodrigues de (2023)
This doctoral thesis focuses on the working and living conditions of black women assisted in the Social Service Technical Sectors of the Domestic and Family Violence Courts against Women of the São Paulo Court of Justice - TJSP. The presupposition, as the central analytical key underpinning the research - the thesis of the thesis - is that slave labor in Colonial and Empire Brazil has traces of continuity and ruptures in the transition to free and salaried labor, which extends to the present day, as a result of the current monopoly capitalist stage, whose particularity in the country is that of dependent and racist capitalism (which overexploits the workforce and pays it below its value). The main objective is to analyze and identify the consequences of this process in the reproduction of the social life of black women assisted at the TJSP, in an attempt to advance and contribute to analyses that deconstruct both the idea of the linear evolution of work (as if it were a continuum) and the working class as a homogeneous and abstract block. To this end, I problematize the main constitutive elements of slave labor in Brazil and the determinations placed on enslaved subjects; I seek to understand how free and salaried labor was constituted in the aftermath of "inconclusive abolition" for black women workers in São Paulo; I then present and analyze the fundamental features of the contemporary configurations of work in Brazil and the repercussions for black women workers, pointing out that the root of the precariousness of working conditions and relations does not originate with the productive restructuring of capital, but in the Brazilian socio-historical formation. In development of the study, in addition to bibliographical and documentary research, I conducted semi-structured interviews based on a script. Ten interlocutors took part in the interview: Maria Rosa, Caçandoca, Mandira, Nhunguara, Camburi, Peropava, Boa Esperança, Pilar, Santa Maria and Saracura, and from them it was possible to infer (in addition to the bibliographical and documentary research) that, although legally the abolition of black slavery was a fact expressed in two articles in a law, the form was changed, but not the content. In other words, the possibility of breaking away from slave labor did not actually materialize for these subjects, considering that, from a political point of view, it was the organization of enslaved workers into Quilombos that eroded the colonial slave system. In view of this finding, another of equal value was to identify, from the racial relations in the labor market from the perspective of whiteness, that the social, sexual and racial divisions of labor (as daughters of racism) have assigned not only the bottom of the social pyramid, but "the place" in the labor market to black women, that is, from being enslaved they have become domestic servants and outsourced cleaners in the service sector. At the end, I highlight the struggles and resistance of black women workers for bread and work, yesterday and today, in the face of the precariousness and barbarity of social life